2011
DOI: 10.1097/mcg.0b013e3181ce5dfa
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Prognosis of Combined Hepatocellular and Cholangiocarcinoma After Curative Resection Comparison With Hepatocellular Carcinoma and Cholangiocarcinoma

Abstract: The results of this study indicated that cHCC-CC had a significantly poorer prognosis than HCC and CC even after curative resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(122 citation statements)
references
References 17 publications
4
116
2
Order By: Relevance
“…The small numbers of patients in the 2 studies preclude us from drawing firm conclusions about the outcomes of these tumor subtypes. In several published studies on liver resection, HCC-CC patients were found to have shorter periods of disease-free survival and poorer prognoses than I-CC patients 2,4,26 and HCC patients. 26 None of the patients in our study experienced lymph node invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The small numbers of patients in the 2 studies preclude us from drawing firm conclusions about the outcomes of these tumor subtypes. In several published studies on liver resection, HCC-CC patients were found to have shorter periods of disease-free survival and poorer prognoses than I-CC patients 2,4,26 and HCC patients. 26 None of the patients in our study experienced lymph node invasion.…”
Section: Discussionmentioning
confidence: 99%
“…In several published studies on liver resection, HCC-CC patients were found to have shorter periods of disease-free survival and poorer prognoses than I-CC patients 2,4,26 and HCC patients. 26 None of the patients in our study experienced lymph node invasion. The poor prognosis of patients with HCC-CC may be due to its inherent aggressiveness, which is linked to the origination of the tumor cells from pluripotent hepatic precursor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the differentiation of hepatic nodules in high-risk patients, the possibility of ICCs should be ruled out [66]. Differentiating ICCs from HCCs with imaging studies is critical because their respective treatment strategies and prognoses are different [67,68]. On ECCM-enhanced imaging, ICCs typically show peripheral or weak enhancement on the HAP and centripetal or persistent enhancement on the PVP and DP [69,70].…”
Section: Hcc Vs Non-hepatocellular Tumorsmentioning
confidence: 99%
“…HCCs with such IRE patterns (IRE-HCCs) were reported in 5-13% of patients undergoing curative resection or radiofrequency ablation [3][4][5]. The IRE pattern is not a typical imaging feature of HCC; it is a finding usually indicative of other hepatic malignancies such as cholangiocarcinoma or combined hepatocellular-cholangiocarcinoma, which generally show worse prognoses than HCC [6,7]. In patients with chronic liver disease, however, a significant proportion of hepatic tumors showing IRE are HCCs, because the incidence of this malignancy is much higher than that of other malignancies with underlying liver diseases [8,9].…”
Section: Introductionmentioning
confidence: 99%